KEEFEKTIFAN PELAKSANAAN SUPERVISI AKADEMIK DAN PENGEMBANGAN PROFESI GURU OLEH KEPALA SEKOLAH DI MAS AL WASLIYAH 22 TEMBUNG - Salsa, Salsabila Fitria; Mia Sri Dwi Yanti; Siti Nurhaliza; Mhd. Aris Syahputra Harahap (CV. Arsy Persada Quality, 2024)
The principal's academic supervision and professional development of teachers are key factors in improving the quality of school education. The study aims to evaluate the effectiveness of the implementation of academic supervision and the development of the teacher profession by the principal in the school. Research shows that effective implementation of academic supervision involves open communication, constructive feedback, and continuing learning. In addition, successful teacher development requires a holistic approach, including high-quality training, mentor support, and continuous reflection. The practical implications of this study emphasize the importance of the headmaster's role as an effective learning leader in improving the quality of school education. In the performance of the teacher's academic supervision and professional development, the principal must have the appropriate skills and skills to direct and supervise teachers. They must have effective communication skills, good analytical capabilities, and good decision-making ability. Furthermore, the headmaster should also have the ability to identify the needs of teachers and students, and develop appropriate strategies to improve the quality of education. In this abstract, we will discuss how the effectiveness of the implementation of academic supervision and the development of a teacher's profession by the principal can enhance the quality of education, and how it applies